The Prague Real Estate Market - Chovanec, Roman; Krejčí, Filip; Milek, Lubomír; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2009)
This thesis is an analysis of the major segments of the real estate market in Prague. It covers office, retail, industrial, hotel and residential real estate and the investment market behind these segments predominantly from the perspective of an institutional investor. In the thesis, theoretical fundamentals behind real estate development are connected to the present state of the market. The thesis provides an overview of the supply and demand, prices, yields, vacancy rates and major trends or developments in each segment. The analysis of the present state of the market is also connected to the economic crisis. The thesis covers both the reasons behind the depressed and dormant state of the market and emerging trends into the years ahead.
Vedoucí práce: Filip Krejčí
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2010
Rok obhajoby 2010
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses